Rescue therapy for chronic hepatitis C virus infection after repeated treatment failures: Impact on disease progression and risk of hepatocellular carcinoma. Issue 4 (28th January 2019) - Hanafy, Amr Shaaban; Soliman, Shaimaa; Abd‐Elsalam, Sherief
Abstract : Aim: Retreatment after previous failure of direct‐acting antivirals for hepatitis C virus (HCV) infection is a challenging decision. The importance of achieving viral eradication on modification of disease progression and outcome, including the risk of hepatocellular carcinoma (HCC), remains a critical issue to be evaluated. Methods: One hundred patients with repeated failure of sofosbuvir and ribavirin or triple therapy with sofosbuvir, ribavirin, and daclatasvir were divided into a study group ( n  = 50) given rescue therapy (sofosbuvir, daclatasvir, simeprevir, and ribavirin) or a control group ( n  = 50) matched for age, sex, and pretreatment variables (Child–Turcotte–Pugh score and Fibrosis‐4 score). Follow‐up was undertaken after the last non‐response to detect serious adverse events, such as hepatic decompensation and development of HCC. Results: The study group achieved sustained virologic response (SVR) in 47 of 50 (94%) patients. The control group had significantly higher HCC rates than the study group (7 vs. 1 patients), with an odds ratio of 5.44. The rescue therapy was associated with significantly longer time to the occurrence of adverse events. Repeated treatment failures were associated with progression of FibroScan values in the control group (21 ± 4.5 vs. 10 ± 1.5 kPa, P  = 0.001); achieving SVR in the study group stopped fibrosis progression despite non‐significant increase from baseline (13.2 ± 3.2 vs. 10.6 ± 0.6, P  = 0.12). Conclusions: Rescue treatment for HCV infection was highly effective in achieving SVR, less expensive than the newer agents, and is associated with diminished risk of serious adverse events, mainly HCC in these patients.